Green HRM and Employee Commitment: The Role of Training, Rewards, and Culture - I Gusti Putu Diva Awatara; Linda Nur Susila; Endang Saryanti (Indonesian Journal of Sustainability Accounting and Management, 2024)
This study aims to analyze the influence of green training, green rewards, and green organizational culture on employee commitment to the environment. It specifically examines the moderating role of green organizational culture and green rewards in this relationship. The research was conducted on employees working in environmentally friendly companies in Surakarta. The population of this study consists of company employees, with a sample of 100 respondents selected through purposive sampling. The sampling criteria targeted employees from companies implementing eco-friendly principles. Data was collected using questionnaires and observations. The analysis was conducted using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with bootstrapping for parameter estimation. The results reveal that green training, green rewards, and green organizational culture have a significant direct effect on employee commitment to the environment. Additionally, green rewards fully mediate the relationship between green training and employee environmental commitment. Similarly, green organizational culture serves as a full mediator between green training and employee environmental commitment. This study highlights the critical role of green human resource practices in fostering employee commitment to environmental sustainability, providing valuable insights for organizations aiming to enhance their environmental performance.